Study the Effect of Multilayer Single Point Incremental Forming on Residual Stresses for Bottom Plates - Abed, Aseel Hamad; Bedan, Aqeel Sabree; Noori, Mohanad Faeq (Al-Khwarizmi Engineering Journal, 2017)
Abstract Knowing the amount of residual stresses and find technological solutions to minimize and control them during the production operation are an important task because great levels of deformation which occurs in single point incremental forming (SPIF), this induce highly non-uniform residual stresses. In this papera propose of a method for multilayer single point incremental forming with change in thickness of the top plate (0.5, 0.7, 0.9) mm and lubrication or material between two plates(polymer, grease, grease with graphite, mos2) to knowing an effect of this method  and parameters on residual stresses for the bottom plates. Also compare these results for the bottom plates with the single plate at same thickness 0.9 mm.The results showed that when increase thickness of the top plate the value of residual stresses will decrease for bottom plates and when used graphite with grease between two plates gives less residual stresses (R.S = 60.173 MPa.) reverse when used Mos2 which will gives a larger residual stresses (R.S = 146.617 MPa.) in the bottom plate.Keywords: Multilayer Single Point Incremental Forming (SPIF), Residual Stresses, Lubrication.